Offshore Minerals For Flue Gas Desulfurization And By-Product Strategic Metals And Superphosphate Fertilizer - J. Robert Woolsey (International Marine Minerals Society, 1992)
This paper provides certain Southeastern coal-burning utilities with an economic strategy for complying with the sulfur dioxide emission standards set firth by the Clean Air Act Amendments of 1990. The strategy takes advantage of the occurrence of vast quantities of manganese nodules on the Blake Plateau offshore Georgia and the Carolinas, a commodity which as been proven to be a highly effective dry sorbent of sulfur dioxide. Using existing technology, manganese nodules could be mined and transported via barge directly to power plant sites, where they would be used as filter material for cleaning sulfur dioxide from the effluents of coal-fired power plants. Completely sulfated filter material could be treated for the extraction of by-product metals such as cobalt, copper, nickel, and manganese. The strategy may well be enhanced by the occurrence of ore grade phosphate rock in the same area of the Blake Plateau. This phosphate rock could be simultaneously mined to effect a reduction in production costs if it is found to be suitable for use as either a direct application fertilizer or as an acidulated superphosphate fertilizer. The manganese nodule-based strategy offers a retrofitting solution for existing power plants that would minimize the capital costs for compliance with the Clean Air Act Amendments and has the added advantage of providing a number of other metal or fertilizer by-products.